2010
DOI: 10.1038/pcan.2009.59
|View full text |Cite
|
Sign up to set email alerts
|

Integrin involvement in freeze resistance of androgen-insensitive prostate cancer

Abstract: Cryoablation has emerged as a primary therapy to treat prostate cancer. While effective, the assumption that freezing serves as a ubiquitous lethal stress is challenged by clinical experience and experimental evidence demonstrating time-temperature related cell death dependence. The age-related transformation from an androgen-sensitive (AS) to an androgen-insensitive (AI) phenotype is a major challenge in the management of prostate cancer. AI cells exhibit morphological changes and treatment resistance to many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
(70 reference statements)
0
10
0
Order By: Relevance
“… 5 , 10 , 33 38 The key to procedural success is dosimetry in terms of temperature and duration of the freeze–thaw cycle. However, a definitive statement of the “cryoablative dose” has been hampered by the diversity of opinions and practices as they relate to a number of variables, including procedural implementation, cooling “power” (heat extraction capacity of the cryogen), the variability in thermal gradients in frozen tissue, regional blood flow, anatomical variation, cancer’s distinct phenotypic responses to a freeze–thaw stress, and the molecular responses of cells of a generically defined “cancer.” 22 , 38 42 Successful CA requires that a targeted volume of tissue be frozen to a lethal target temperature less than −20°C to −40°C (cancer-type dependent) to assure complete lethality throughout the targeted mass. 12 , 26 , 40 , 43 To achieve this goal, a 1-cm positive freeze margin around the targeted tissue volume is typically implemented to assure delivery of a lethal temperature at the tumor margin or risk an increased chance of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 10 , 33 38 The key to procedural success is dosimetry in terms of temperature and duration of the freeze–thaw cycle. However, a definitive statement of the “cryoablative dose” has been hampered by the diversity of opinions and practices as they relate to a number of variables, including procedural implementation, cooling “power” (heat extraction capacity of the cryogen), the variability in thermal gradients in frozen tissue, regional blood flow, anatomical variation, cancer’s distinct phenotypic responses to a freeze–thaw stress, and the molecular responses of cells of a generically defined “cancer.” 22 , 38 42 Successful CA requires that a targeted volume of tissue be frozen to a lethal target temperature less than −20°C to −40°C (cancer-type dependent) to assure complete lethality throughout the targeted mass. 12 , 26 , 40 , 43 To achieve this goal, a 1-cm positive freeze margin around the targeted tissue volume is typically implemented to assure delivery of a lethal temperature at the tumor margin or risk an increased chance of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] For instance, in prostate cancer, the loss of androgen receptor expression (shift from hormone responsive to unresponsive cancer) or increase in integrin expression can result in increased tolerance to freezing, shifting the minimal lethal temperature from −25°C to −40°C. 26,30 As such, for prostate cancer, a minimal lethal temperature of −40°C is typically targeted to assure complete cancer ablation. 16,19,27 In vitro studies have identified −20°C as the minimal lethal temperature for colorectal cancer 31,32 ; −25°C for renal cancer, 29,33 pancreatic cancer, 34,35 and bladder cancer 36,37 ; and −35° for liver cancer.…”
mentioning
confidence: 99%
“…[33][34][35][36] For this purpose, cytotoxic drugs, antifreeze proteins, chemical agents, immunologic enhancing drugs, TNF alpha, and others have been used. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Irradiation has also been utilized. The timing for use of these agents in relation to the cryoablative procedure is not well established, but all contribute to cell death by apoptosis.…”
Section: Increasing Tissue Destructionmentioning
confidence: 99%
“…20,21,32,35,36 While an ongoing area of research, several studies have shown promise in elevating the minimal lethal temperature for prostate cancer from -40°C to approaching -10°C in in vitro and murine models using calcitriol pre-treatment. [48][49][50][51][52] More recent studies have focused on the combination of immunotherapy and cryoablation to improve cancer destruction, both localized and metastatic disease. 44,[53][54][55] Regardless of the agent utilized, the goal of these efforts is to "make ice lethal at 0°C" while eliciting minimal side effects.…”
Section: Increasing Tissue Destructionmentioning
confidence: 99%